New species of Culicoides, description of female of Culicoides pseudocrescentis Tavares & Luna Dias and new record of Culicoides castillae Fox from Southeastern Brazil (Diptera: Ceratopogonidae) - Felippe-Bauer, Maria Luiza; Santarém, Maria Clara Alves; Macedo, Antonio Carlos Cruz; Okuda, Liria Hiromi (Zootaxa, 2024)
A new species of Culicoides, C. andradinensis Felippe-Bauer & Santarém is described and illustrated based on female specimens from the municipality of Andradina, São Paulo state, Brazil. The new species is placed in the limai species group and compared with their related congeners. The description of females of Culicoides pseudocrescentis Tavares & Luna Dias based on specimens from Brazilian states of Espírito Santo and São Paulo is given. Culicoides castillae Fox is first recorded from Brazil. All studied specimens are deposited in the Ceratopogonidae Collection of Fundação Oswaldo Cruz, Brazil (Fiocruz/CCER).